The Utilization of Carboxymethyl Cellulose (Cmc) from Groundnut (Arachis Hypogaea L) Cellulose as Stabilizer for Cow Milk Yogurt - Sebayang, Firman (Talenta Publisher, 2019)
The utilization of carboxymethyl cellulose (CMC) from groundnut (Arachis hypogaea L) cellulose as stabilizer for cow milk yogurt has been done in three steps. The first step was α-cellulose isolation from groundnut skin powder which was analysed with FTIR. The result was compared to FTIR analysis of commercial cellulose to verify the compound obtained is cellulose. The second step involves alkalization process using isopropanol and NaOH, carboxymethylation process with sodium chloroacetate (NaMCA), neutralization using CH3COOH 90% and ethanol, purification with aquadest and followed by centrifugation and addition of acetone to produce carboxymethyl cellulose. The CMC produced gave positive result in the qualitative anlysis, the FTIR spectrum was similar to commercial CMC and the degree of substitution obtained was 0.71. The last step is yogurt making process. In this stage, the CMC concentration added was varied from 0 – 0.5%. Then, the yogurt produced went through quality analysis such as syneresis, pH, viscosity, protein, fat content and organoleptic tests. The best result was obtained at the addition of 0.5% CMC concentration with 7.69% and 2.11% protein and fat content, pH 4.6, viscosity was 1676.01 x 102 cP, low syneresis with 90.66% stability and 22 days of storage life. Organoleptic result shows that yogurt with 0.3% CMC addition gave the best result with distinctive aroma and sourness, and rather thick texture. The panelists preferred such yogurt to others. The quality analysis for yogurt with CMC stabilizer still meets SNI standard. [Use 10 pt Times New Roman for the abstract body with single spacing and 10 pt spacing for the next heading. Left indent is 2 cm and right indent is 0 cm. Please write abstract paper in English with maximum length is 200 words.